'Social Care Told me I Had to': Empowerment And Responsibilization in The Domestic Violence Disclosure Scheme. (14th July 2021) - Hadjimatheou, Katerina
Abstract: Domestic Violence Disclosure Schemes (DVDS), recently introduced in many jurisdictions, aim to empower victim-survivors of domestic abuse by giving them access to information about their partner's criminal history. This paper presents findings from the largest study of the police implementation of the first such scheme, introduced in the United Kingdom in 2014. It finds that the disclosure process is increasingly being shaped by a child protection agenda that makes victim-survivors responsible for protecting their children from the harms of domestic abuse. It examines tensions and dilemmas this raises for police seeking to safeguarding and empower victim-survivors, and draws on feminist ethical theory to develop a more nuanced understanding of the dynamics between the professional spheres of domestic abuse and child protection.